2015
DOI: 10.1158/1535-7163.mct-15-0025
|View full text |Cite
|
Sign up to set email alerts
|

HMDB and 5-AzadC Combination Reverses Tumor Suppressor CCAAT/Enhancer-Binding Protein Delta to Strengthen the Death of Liver Cancer Cells

Abstract: Hepatocellular carcinoma (HCC) can arise from chronic inflammation due to viral infection, organ damage, drug toxicity, or alcohol abuse. Moreover, gene desensitization via aberrant CpG island methylation is a frequent epigenetic defect in HCC. However, the details of how inflammation is linked with epigenetic-mediated desensitization of tumor suppressor genes remains less investigated. In this study, we found that loss of CEBPD enhances the growth of liver cancer cells and is associated with the occurrence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Currently, to the best of our knowledge, no conclusive study of the expression levels of C/EBPδ in GC cells has been performed. In liver cancer, C/EBPδ acts as a tumor suppressor (20). In the present study, C/EBPδ was downregulated in GC cells, indicating that C/EBPδ acted as a tumor suppressor.…”
Section: Discussionsupporting
confidence: 58%
“…Currently, to the best of our knowledge, no conclusive study of the expression levels of C/EBPδ in GC cells has been performed. In liver cancer, C/EBPδ acts as a tumor suppressor (20). In the present study, C/EBPδ was downregulated in GC cells, indicating that C/EBPδ acted as a tumor suppressor.…”
Section: Discussionsupporting
confidence: 58%
“…As depicted, over-expressing PDGFR-alpha reduces melanoma and endothelial cell number by affecting several molecular functions (such as Cell-growth and proliferation ; Cell Death and Survival , Cell Signaling ) via up- and down- regulation of several interconnected molecules. Namely, CXCL10/IP-10, miRNA-503, CEBPB and CEBPD, two known onco-suppressor genes [50, 51, 53, 54, 52] were found strongly modified in cells over-expressing PDGFR-alpha, along with other molecules such as CXCL8, IL6, SOCS3, all known to have functional connections with CXCL10/IP-10.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Our previous studies suggested that CEBPD is responsive to anticancer drugs (26,27). We further assessed whether CDDP affected CEBPD expression in UCUB cells.…”
Section: Significance Of Cebpd Immunoreactivity In Ucubmentioning
confidence: 97%